PD-1 Bispecific Killer Engager (PD-1 BiKE) effectively depletes effector T lymphocytes in experimental autoimmune encephalomyelitis - Naatz, Lauren C.; Dong, Shuyun; Zhai, Yujia; Evavold, Brian; Chen, Mingnan (Frontiers in Immunology, 2025)
BackgroundBispecific killer engagers (BiKEs), which harness natural killer cells to deplete target cells, have garnered success in ablating tumor cells but have not been well explored in eliminating primary cells, such as effector cells in autoimmune diseases. Previously, we reported a BiKE that targeted human lymphocytes expressing programmed death-1 (PD-1). The BiKE was shown to promote NK cell-mediated depletion of PD-1+ cells in vitro. Here, we posited that a mouse-specific PD-1 BiKE could be used as a tool to deplete PD-1+ cells in vivo.MethodsPD-1 BiKE was designed and produced in an IgG-like format. The BiKE was characterized for its functional binding, ability to facilitate NK cell-PD-1+ cell-cell interactions, and depletion of PD-1+ cells using several in vitro assays. The BiKE was then evaluated for its ability to deplete PD-1+ T cells in vivo using an EL4 tumor model, and the EAE model.ResultsPD-1 BiKE demonstrated selective binding to PD-1+ T cells encompassing both a cell line (EL4) and primary cells. PD-1 BiKE simultaneously engaged its two targets, PD-1+ and NK cells, and mediated a 63% increase in cell-cell interactions between the two targets. In co-cultures of primary PD-1+ T cells and NK cells, the BiKE reduced the number of T cells by 28%. Importantly, PD-1 BiKE did not reduce PD-1- T cells when co-cultured with NK cells. In vivo, PD-1 BiKE reduced the fraction of inoculated EL4 cells by ~53%. In EAE mice, PD-1 BiKE reduced the average number of primary PD-1+ T cells by 56% and 65% in the spinal cords and brains, respectively. Beyond the IgG-like BiKE, two non-IgG-like BiKEs were also designed and generated and demonstrated strong but distinct binding to PD-1 and CD16.ConclusionsThe IgG-like PD-1 BiKE bound to both cellular targets, CD16 and PD-1, and was able to deplete primary PD-1+ T lymphocytes in the EAE model. Altogether, the work showcases the effectiveness of using BiKEs to deplete non-malignant cells.